ANALISIS PEDAGOGI KRITIS PAULO FREIRE DI SEKOLAH FORMAL - Rizqi Sofiana; Jannatan Maulana Khasri; Dina Zahra Maharani (Tazkiya: Jurnal Pendidikan Islam, 2025)
This research aims to analyze and explore the implementation of Paulo Freire's critical pedagogy within the context of formal schooling, which is currently dominated by the "Banking Education" phenomenon. Amidst the gap between the idealism of education as a process of humanization and the reality of schools as tools of domestication, this article examines how Freirean concepts can be integrated to overcome rigid educational standardization. The method employed in this study is descriptive qualitative with a library research approach. The findings indicate that the implementation of the "Problem-Posing Education" method and the cultivation of conscientization (critical consciousness) are key to transforming students' roles from passive objects into active subjects. Despite the challenges of curriculum standardization, the praxis of critical pedagogy can be realized if teachers position themselves as transformative intellectuals. The study concludes that transforming formal schools into "humanity laboratories" requires the courage to implement dialogue and dismantle the barriers between the classroom and social reality. Consequently, education can guide students to not only be proficient in "reading the word" but also critical in "reading the world.